2023
DOI: 10.1088/2631-8695/acd23a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fin width on nano scale tri-gate FinFET including the quantum mechanical effect

Abstract: An inversion charge-based threshold voltage model is proposed for 10 nm channel length Tri-gate (TG) FinFET. The variation threshold voltage has been studied with respect to fin width W f … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The physical parameters which determine the performance of FinFETs include not only the channel length and width but also the height and width of the fin. Suparna et al proposed inversion charge based threshold voltage model [6]. Pidaparthy et al reported the imact of fin height, width and channel length on the electrical performance parameters [7].…”
Section: Introductionmentioning
confidence: 99%
“…The physical parameters which determine the performance of FinFETs include not only the channel length and width but also the height and width of the fin. Suparna et al proposed inversion charge based threshold voltage model [6]. Pidaparthy et al reported the imact of fin height, width and channel length on the electrical performance parameters [7].…”
Section: Introductionmentioning
confidence: 99%